PRESENT-DAY EMPLOYERS’ REQUIREMENTS TO SPECIALISTS HAVING BSc DEGREE - ТІТЕНКО, А. В.; МАКСИМЕНКО, Н. В.; НЕКОС, А. Н.; УТКІНА, К. Б. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 1970)
In the framework of the implementation of Tempus project “Qualifications Frameworks for Environmental Science at Ukrainian Universities  - QANTUS” a questionnaire was developed and UA employers’ opinion poll was conducted. The questionnaire contains a list of competences which are necessary for specialist having BSc for successful work in organizations and companies of various types. Based on obtained results, the rating of competencies was compiled and three categories of competences (depending on the level of importance) were identified for specialist having BSc (ecology, environmental protection and balanced nature use) for successful employment. Key employers’ priorities have were identified.